The Implementation of the Discussion Method in Improving Vocabulary Mastery of Eighth Grade Students at Islamic Junior High School Mazra’atul Ulum Paciran Lamongan - Izzatun Nisa' Izzatun Nisa'; Fiqih Aisyatul Farokhah (Institut Agama Islam Tarbiyatut Tholabah, 2026)
This study was designed to determine the improvement of vocabulary of eighth-grade students of MTs Mazraatul Ulum Paciran through the implementation of the discussion method with the implementation of two cycles. This study employed a Classroom Action Research approach, comprising planning, action, observation, and reflection. The research subjects were 8th-grade students of MTs Mazraatul Ulum Paciran. Data on students' vocabulary mastery were collected through tests each cycle. The results showed an increase in students' vocabulary after implementing the discussion method in two cycles. In Cycle I, there was an average increase of 78% in vocabulary mastery among students. However, after reflection and improvement in Cycle II, there was a more significant increase in the average score of 80%. Therefore, it can be concluded that the implementation of the discussion method is effective in improving the vocabulary of grade 8 students of MTs Mazraatul Ulum Paciran after two cycles of action